Sold American : Consumption and Citizenship, 1890-1945 - McGovern, Charles (Book collections on Project MUSE., 2006)
At the turn of the twentieth century, an emerging consumer culture in the US promoted constant spending to meet material needs and develop social identity and self-cultivation. In 'Sold American', Charles McGovern examines the key players active in shaping this cultural evolution: advertisers and consumer advocates. He argues that even though these two professional groups invented radically different models for proper spending, both groups propagated mass consumption as a specifically American social practice and an important element of nationality and citizenship.